Neonatal hematological parameters and the risk of moderate-severe bronchopulmonary dysplasia in extremely premature infants - Xueyu Chen; Huitao Li; Xiaomei Qiu; Chuanzhong Yang; Frans J. Walther (BMC, 2019)
Abstract Objective To evaluate the association between hematological parameters at birth and the risk of moderate-severe bronchopulmonary dysplasia (BPD) in a cohort of extremely preterm infants. Methods This is a retrospective study of all extremely premature infants admitted to the neonatal intensive care unit, Shenzhen Maternity and Child Healthcare Hospital from January 2016 to May 2018. Extremely prematurity was defined as a delivery at a gestational age ≤ 28 weeks or a birth weight ≤ 1000 g. BPD was diagnosed if oxygen exposure exceeded 28 days and the severity was decided at 36 weeks PMA or discharge. Multivariable analysis was performed to assess the independence of the association between hematological parameters at birth and risk of moderate or severe BPD. Results A total of 115 extremely premature infants were analyzed in this study. The median platelet count, neutrophil and monocyte count at birth were significantly higher in infants with moderate-severe BPD compared to infants without BPD (228 vs 194*109/l, P = 0.004; 5.0 vs 2.95*109/l, P = 0.023; 0.88 vs 0.63*109/l, P = 0.026, respectively) whereas the mean platelet volume was significantly lower in infants with moderate-severe BPD than those without BPD (9.1 vs 9.4 fl, P = 0.002). After adjusting for covariates, the risk of moderate-severe BPD was independently associated with platelet count≥207*109/l (odds ratio 3.794, 95% confidence interval: 1.742-8.266, P = 0.001). Conclusion Our findings suggest that hematologic parameters at birth are different in extremely preterm infants who will develop moderate-severe BPD. A higher platelet count at birth may increase the risk of moderate-severe BPD after extremely premature birth.